How digital consumers counter the threat to their privacy and security posed by Big Data - Simões Alves, Nuno Gabriel (2022)
The main objective of this thesis is to understand how digital consumers feel regarding the threats Big Data analytics poses to their personal information. To achieve that, a primary qualitative approach was conducted, where 18 web services regular users were questioned about the topic. The responses were individually transcribed, coded, and analyzed, which allowed for the comparison of insights from different age and income level groups. It was discovered that individuals from the youngest age group feel comfortable sharing non-sensitive personal information, whereas respondents with ages above 35 years old are not. Participants with monthly income levels above 1500 euros demonstrated negative feelings regarding the future scenario of online personal privacy. From now on, all the entities need to be informed and aware of the dangers posed by Big Data analytics to the privacy of digital users and aim to create a safe and prosperous online data collection environment.